DNA Barcoding for Selected Mangrove-Based Estuary Fishes from Way Kambas National Park, Lampung Province, Indonesia - Ariyanti, Yanti; Rini, Ika Agus; Oktaviani, Indah; Leksikowati, Sovia Santi (Journal of Tropical Life Science, 2021)
Over the past decade, DNA barcoding has provided new insight into fish ecology and biosystematics and led to new species' discovery. DNA barcoding is a method for the recognition and identification of species using short, standardised DNA fragments. The correct taxonomic identification of species is critical for the assessment and monitoring of biodiversity. This study applied DNA barcoding techniques to identify selected fish species from a mangrove-based estuary in Way Kambas National Park, Lampung Province, Indonesia. The gene encoding cytochrome c oxidase subunit I (COI) was amplified and bi-directionally sequenced from 22 specimens. The resulting 680 base pairs (bp) sequence was used to identify species, obtain phylogenetic information, and analyse genetic distances. A neighbour-joining tree was constructed based on the mitochondrial COI gene using the Kimura two-parameter model. This study also exhibits conservation status for those identified species. Our findings will facilitate future studies of fish species diversity in mangrove estuary-based ecosystems and provide preliminary data in policymaking in conservation areas such as National Park.